Determination of theft in Russia and Belarus criminal codes: history and actualness - Grountov, Igor; Yeliseyev, Sergey (Journal of the Belarusian State University. Law, 2019)
In the article questions of understanding and determination of theft in criminal codes of Russia and Belarus are considered. Directions of improvement of crimes statutories for this type of property crimes are offered.
Keywords: Grand Duchy of Lithuania Statutes; Penal code of the Russian Empire; theft; covert embezzlement; stealage